PENGARUH DONGENG DALAM MASA KANAKKANAK TERHADAP PERKEMBANGAN SESEORANG - Hidayat, Arif (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2009)
this article dedicated to describe childhood’s tale effect to ones development on his life. It’s because there are concept thatembodied inside tale that can construct child character. Concepts are frame of mind that becomes reference. Inside tale, those concepts canrealize through pragmatism moral message. Tale usually told at childhood age that in psychological perspective is basic time for childdevelopment. Concept that planted firmly from early age can reemerge into memory as thoughts or ideas